KARAKTERISTIK MORFOLOGI DAN PERKEMBANGAN BUNGA Aeschynanthus tricolor Hook. (GESNERIACEAE) - Sri Rahayu; Hary Wawangningrum; R. Vitri Garvita (BERITA BIOLOGI, 2015)
Aeschynanthus tricolor Hook. (Gesneriaceae) is one of the Aeschynanthus, a special lipstick flower characterized by its campanulate red calyx which more showy than its short stripped corolla. This specific character is beneficially potential for cross pollination to make a new variety. To develop a new variety, it is important to have information about the biology of flowers.However, such information is still lacking. This research was therefore aimed to obtain information on flower characteristics and development in order to understand the pollination systems of this species. Observations was made on A. tricolor from Central Kalimantan collected in 2000 that was planted in Bogor Botanic Gardens green house. Results indicated that this species was categorized as protandrous, which mean the flower cannot pollinate by itself without pollination agent. The pollinators of this species were bird and/or bumble bee. The flower developments took 32 days from the beginning of a flower bud to anthesis. It was suggested that cross pollination for interspecific hybridization was between the species within the same clade (Section Aescynanthus).